The effect of yoga and zumba exercises in increasing VO2 max - Yasinta Aldinata Arsy; Ali Multazam; Siti Ainun Marufa (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Someone with a healthy and fit body is likely to be able to do a high level of physical activity. Physical exercise can improve physical fitness and has an important element, cardiorespiratory endurance. One way to measure cardiorespiratory endurance is by measuring the maximum volume of oxygen consumption, called VO2 max. Methods: This type of research uses a quasi-experimental type, namely two pre-and post-test design research groups. The type of quasi-experimental research design uses two groups of subjects, namely group A, who are given yoga exercises, and group B, who are given zumba exercises, with a total of 30 respondents. The cardiorespiratory endurance was measured with the beep test. Results: Based on the paired sample t-test, the San Zumba yoga group had a result of p<0.05. Whereas in the independent sample T-Test test, the results of p<0.05, it can be concluded that there is a significant difference in the increase in the yoga and zumba groups. Conclusion: There are differences in the effect of giving yoga and zumba exercises on increasing VO2 max values.